Answer:
![\text{Average rate}=\frac{\text{40 laps}}{\text{ hour}}](https://tex.z-dn.net/?f=%5Ctext%7BAverage%20rate%7D%3D%5Cfrac%7B%5Ctext%7B40%20laps%7D%7D%7B%5Ctext%7B%20hour%7D%7D)
Step-by-step explanation:
Please consider the complete question.
Sebastian swan laps every day in the community swimming pool. He swam 45 minutes each day, 5 days each week, for 12 weeks. In that time, he swam 1800 laps. What was his average rate in laps per hour?
Let us convert time taken into hours as:
![\text{Days}=5\times 12=60](https://tex.z-dn.net/?f=%5Ctext%7BDays%7D%3D5%5Ctimes%2012%3D60)
![\text{Minutes}=60\times 45](https://tex.z-dn.net/?f=%5Ctext%7BMinutes%7D%3D60%5Ctimes%2045)
1 hour = 60 minutes. To convert minutes into hours, we will divide total minutes by 60.
![\text{Hours}=\frac{60\times 45}{60}=45](https://tex.z-dn.net/?f=%5Ctext%7BHours%7D%3D%5Cfrac%7B60%5Ctimes%2045%7D%7B60%7D%3D45)
Now, we will divide 1800 by 45 to find average rate in laps per hour as:
![\text{Average rate}=\frac{\text{1800 laps}}{\text{45 hours}}](https://tex.z-dn.net/?f=%5Ctext%7BAverage%20rate%7D%3D%5Cfrac%7B%5Ctext%7B1800%20laps%7D%7D%7B%5Ctext%7B45%20hours%7D%7D)
![\text{Average rate}=\frac{\text{40 laps}}{\text{ hour}}](https://tex.z-dn.net/?f=%5Ctext%7BAverage%20rate%7D%3D%5Cfrac%7B%5Ctext%7B40%20laps%7D%7D%7B%5Ctext%7B%20hour%7D%7D)
Therefore, Sebastian's average rate is 40 laps per hour.
The answer is 180 square yards, or 20 square feet.
Answer
sheeesh
Step-by-step explanation:
sheeeeeeeeeeeeeeeeeeeeeeeeesh
Y - y1 = m( x - x1); where m = (y2 - y1)/(x2 - x1);
We have m = (6-0)/(7-5) = 6 / 2 = 3 ;
The equation of the line is: y - 0 = 3(x-5);
Finally: y = 3x - 15.
Answer:
The factors of x^2+3x-4 are (x-1)(x+4) ....
Step-by-step explanation:
We have to find the factors of x^2+3x-4
As we know that this is a quadratic equation.
So we have to find the roots first.
The roots are -1 and 4.
Now completing the quadratic formula using the roots we have :
x^2+4x-x-4
Make a pair of first two terms and last two terms:
(x^2+4x)-(x+4)
Now take out the common from each pair:
x(x+4)-1(x+4)
(x-1)(x+4)
Thus the factors of x^2+3x-4 are (x-1)(x+4) ....